Characterization of organic fluorophores for in vivo FRET studies based on electroporated molecules. - Plochowietz, A; Crawford, R; Kapanidis, A (2014)
In vivo single-molecule fluorescence and Förster resonance energy transfer (FRET) techniques are excellent tools for studying spatial distribution, the nanoscale structure and conformational changes in living cells. We have recently introduced an electroporation-based method to internalize DNA and proteins labeled with organic fluorophores into living bacteria and established the ability for long-lived single-molecule fluorescence and FRET measurements. However, further developments, such as optimization of electroporation conditions, evaluation of organic fluorophore performance in vivo and quantitative single-cell FRET analysis, are needed to make the method more robust and general. Using singly-labeled DNA fragments, we optimized internalization efficiency and cell viability at six electroporation voltages, achieving >60% loading and viability similar to non-treated cells. We characterized the photostability and brightness of three donor fluorophores and four acceptor fluorophores in vivo; Cy3B, Atto647 and Atto647N performed best with photobleaching lifetimes of ∼20 s, 46 s and 92 s, respectively, and brightness values of ∼4000 photons per second under the same illumination conditions. We used three doubly-labeled DNA FRET standards (having in vitro FRET efficiencies of ∼17%, ∼42%, and ∼88%) and an alternating-laser excitation scheme to measure apparent FRET efficiencies at the single-cell level. We showed that we could differentiate DNA FRET standards at the single-cell level. Our approach offers a powerful method for the study of intramolecular changes or complex formation using FRET at the single-cell level in live bacteria.